Proactive stress interference mechanism and its application in the Mahu oil area, Junggar basin - Wang, Shuo; Li, Xiaoshan; Hao, Lihua; Zhang, Xiaogong; Zhang, Lifeng; Song, Junqiang; Liu, Rongjun; Pan, Hong; Gu, Kaifang; Li, Ting; Luo, Guanxing; Wang, Xin; et al. (Frontiers in Earth Science, 2022)
There exists a large horizontal principal stress difference (11–38 MPa) in the tight conglomerates in the Mahu oil area, China. It is difficult to form a complex fracture network via hydraulic fracturing under these conditions. To improve reservoir stimulation, the fracture formation mechanism of the complex conglomerate fracture networks was explored. Based on the geo-mechanics theory of fracture formation, the mechanism of the "stress wall" formed by fracturing in horizontal wells was analyzed in this paper. The inhibitory effect of the stress wall on the formation of tensile and shear fractures was studied. The reason for the decrease in the stress difference coefficient caused by fracturing fluid was analyzed through numerical simulation, which suggested that the complexity of a fracturing network is mainly controlled by the interference of externally applied stress and the reduction in the coefficient of internal stress difference. In this paper, by proactively introducing stress interference in the application of the Ma131 small-well-spacing pilot area, innovative technologies were developed, including optimization of the 3-D staggered small-well-spacing pattern, synergetic optimization of multiple elements and zipper fracturing. The positive effects of proactive stress interference on improving fracturing volume, reserve utilization rate and recovery were discussed. Based on the concept of proactive stress interference, the “serial fracturing mode” of horizontal wells was proposed to reduce drilling and fracturing interference and improve the development effect.